Teaching games for understanding and student learning outcomes in school physical education: a systematic review of experimental and quasi-experimental studies (2020–2025) - Gemi Candra; Jeki Haryanto (Indonesian Institute For Counseling, Education and Therapy, 2025)
Models-based practice has repositioned Teaching Games for Understanding (TGfU) as a leading game-centred alternative to technique-led instruction in school physical education (PE); however, evidence on the learning outcomes it produces remains dispersed and methodologically uneven. This systematic review synthesises experimental and quasi-experimental studies to determine which learning outcomes TGfU has been used to influence and how effective it appears to be in school settings. The review followed the PRISMA 2020 framework. A structured Boolean search of the Scopus database identified 168 records, screened against predefined inclusion and exclusion criteria covering language, document type, publication period (2020–2025), population, study design and topical relevance. Eligibility was restricted to experimental and quasi-experimental interventions measuring student learning outcomes in K–12 school PE. After duplicate removal, title and abstract screening, and full-text assessment, 23 studies were retained for synthesis. Methodological quality was appraised with the FICO framework (Focus, Information, Context, Outcome), and because the included studies used heterogeneous outcomes and instruments, the evidence was combined through thematic synthesis rather than meta-analysis. Two principal findings emerged: first, TGfU and its hybrid configurations consistently improved motivational and psychosocial outcomes, including enjoyment, perceived competence and self-determined motivation; second, effects on physical fitness, motor competence, tactical knowledge and technical skills were generally positive but more variable and dependent on intervention duration and design. The evidence base is geographically concentrated and dominated by short quasi-experimental designs. The review consolidates intervention evidence, informs teacher education and curriculum design, and calls for longitudinal, adequately powered and fidelity-controlled trials.